Multicenter evaluation of complex urinary diversion for renal transplantation: outcomes of complex surgical solutions - Flegar, Luka; Huber, Johannes; Putz, Juliane; Thomas, Christian; Apel, Hendrik; Wullich, Bernd; Friedersdorff, Frank; Fechner, Guido; Ritter, Manuel; Kernig, Karoline; Weigand, Karl; Heynemann, Hans; et al. (World Journal of Urology, 2024)
Purpose: An abnormal lower urinary tract poses significant challenges for transplant surgeons. Besides the ureteral anastomosis to an ileal conduit, there are diverse complex reconstructive solutions. Due to its rarity, standardization and teaching of complex urinary diversion is extremely difficult. Methods: The indications and outcomes of complex urinary diversions after kidney transplantation (KT) were retrospectively investigated at eight urologic transplant centers including a current follow-up. Results: Of 37 patients with 21 (56%) males, vesicoureteral reflux (24%), spina bifida (22%), and glomerulonephritis (12%) were the most common causes of terminal renal failure. In 30 (81%) patients, urinary diversion was performed before KT, at a median of 107.5 (range, 10; 545) months before. Transplantations were held at a median patient age of 43 (10; 68) years, including six (16%) living donations. Urinary diversion was modified during 12 (32%) transplantations. After KT, the ileal conduit was the most common incontinent urinary diversion in 25 (67%) patients; a Mainz pouch I and bladder augmentation were the most frequent continent diversions (each n = 3). At a median follow-up of 120 months (range 0; 444), 12 (32%) patients had a graft failure with a 5-year graft survival of 79% (95%CI 61; 90). The median overall survival was 227 months (168; 286) and the 5-year overall survival 89% (69.3; 96.4). Conclusion: The mid-term kidney transplant function with complex urinary diversion appears to be comparable to transplants with regular urinary diversions. Hence, complex urinary diversion should always be considered as a surgical option, even during transplantation, if necessary.
CRIS-Team Scopus Importer:2024-04-26
Keywords: Dialysis; Ileal conduit; Kidney transplantation; Renal insufficiency; Urinary diversion